KETERLIBATAN MASYARAKAT DALAM PENGELOLAAN WISATA ALAM HULU DAYEUH DI KAWASAN TAMAN NASIONAL GUNING CIREMAI - Armansyah, Ega; Nasihin, Iing; Herlina, Nina (Faculty of Forestry and Environment, Universitas Kuningan, 2023)
Trijaya Village is one of the villages located in Mandirancan District, Kuningan Regency. This village has natural potential that has the potential to be developed as a tourist spot because it already has natural tourist destinations such as the Hulu Dayeuh Camping Ground. This study aims to determine the level of community involvement in the management of Hulu Dayeuh natural tourism. This study uses questionnaires and interviews with the community or samples that have been determined using the Slovin formula. The results of this study indicate that Community Involvement in the Management of the Hulu Dayeuh Nature Tourism is categorized as low, this can be seen from several responses from the community who gave answers to questionnaires starting from Planning, Organizing, Actuatting, and Controlling.Desa Trijaya merupakan salah satu desa yang berada di Kecamatan Mandirancan Kabupaten Kuningan. Desa ini memiliki potensi alam yang berpontensial untuk dikembangkan sebagai tempat wisata karena sudah memiliki destinasi wisata alam seperti Bumi Perkemahan Hulu dayeuh. Penelitian ini bertujuan untuk mengetahui tingkat keterlibatan masyarakat dalam pengelolaan wisata alam Hulu Dayeuh. Penelitian ini menggunakan metode kuisioner dan wawancara terhadap masyarakat atau sampel yang telah ditentukan dengan menggunakan rumus slovin. Hasil penelitian ini menunjukan bahwa Keterlibatan Masyarakat Dalam Pengelolaan Wisata Alam Hulu Dayeuh dikategorikan rendah hal ini dilihat dari beberapa respon masyarakat yang memberikan jawaban kuisioner yang dimulai dari Planning, Organizing, Actuatting, dan Controlling.